Security Aspects for Business Solution Development on Portal Technology - Ovidiu RĂDUTĂ; Adrian MUNTEANU (Database Systems Journal, 2012)
In the scope of portal development, in order to talk about security issues, concerns, and solutions, it is necessary to define a few terms: authentication, authorization, Single Sign-On (SSO), confidentiality, integrity, and non-repudiation. Focusing on the scope of what the portal developer and designer need to know, below it will be explained these concepts, considering it is important to define and make a brief analysis of these terms for understanding of achieving the security goals.